THE EFFECT OF MINERAL FERTILIZER ON THE YIELD OF THE “S-01” COTTON VARIETY UNDER MEADOW-GRAY SOIL CONDITIONS - Xidirovich, Hamraev Fayzulla (Research Focus International Scientific Journal, 2026)
The article investigates the cultivation of cotton under meadow-gray soil conditions of farms specialized in cotton production in the Navoi region, focusing on the application of potassium fertilizer at a rate of 120 kg/ha (K2O) against the background of N-250 and P-175 kg/ha. The study demonstrates that potassium fertilizer creates the most favorable nutritional environment for the growth and development of the “S-01” cotton variety. Under the given conditions, it ensures the possibility of obtaining a high and high-quality cotton yield.